Antagonistic circuits mediating infanticide and maternal care in female mice - Mei, Long; Yan, Rongzhen; Yin, Luping; Sullivan, Regina M.; Lin, Dayu (Nature (London), 2023)
In many species, including mice, female animals show markedly different pup-directed behaviours based on their reproductive state 1 , 2 . Naive wild female mice often kill pups, while lactating female mice are dedicated to pup caring 3 , 4 . The neural mechanisms that mediate infanticide and its switch to maternal behaviours during motherhood remain unclear. Here, on the basis of the hypothesis that maternal and infanticidal behaviours are supported by distinct and competing neural circuits 5 , 6 , we use the medial preoptic area (MPOA), a key site for maternal behaviours 7 – 11 , as a starting point and identify three MPOA-connected brain regions that drive differential negative pup-directed behaviours. Functional manipulation and in vivo recording reveal that oestrogen receptor α (ESR1)-expressing cells in the principal nucleus of the bed nucleus of stria terminalis (BNSTpr ESR1 ) are necessary, sufficient and naturally activated during infanticide in female mice. MPOA ESR1 and BNSTpr ESR1 neurons form reciprocal inhibition to control the balance between positive and negative infant-directed behaviours. During motherhood, MPOA ESR1 and BNSTpr ESR1 cells change their excitability in opposite directions, supporting a marked switch of female behaviours towards the young. ESR1-expressing cells in the principal nucleus of the bed nucleus of stria terminalis are necessary, sufficient and naturally activated during infanticide, and they form reciprocal inhibition with the maternal cells to control young-directed behaviours in female mice.